Attitudes about science and conceptual physics learning in university introductory physics courses - Marina Milner-Bolotin1 (American Physical Society, 2011)
This paper examines the results of the repeated administration of the Colorado Learning Attitudes about Science Survey (CLASS) in a large introductory physics course at a midsize, metropolitan Canadian university. We compare the results to those obtained previously in comparable courses at the University of British Columbia (Canada) and the University of Colorado (U.S.). Atypically, students in this study exhibited a positive shift in their attitudes about science over the semester. The change in students’ attitudes across the term appears to be moderated by their educational background—specifically, whether they had taken grade 12 physics or not. The correlation between students’ attitudes and their conceptual knowledge also appears to be influenced by students’ educational background. The results have pedagogical implications for instructors of introductory college and university physics and potentially for other science courses.